UPAYA PEMERINTAH DESA MEMBANGUN DESA BONAI KECAMATAN BONAI DARUSSALAM KABUPATEN ROKAN HULU TAHUN 2020-2024 - Maysari, Siti; ,, Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Village development efforts are a national goal to create independence and community welfare, making villages the subject of development as mandated by Law No. 6 of 2014 concerning Villages. In Rokan Hulu Regency, one example of this success is seen in Bonai Village, Bonai Darussalam District, which succeeded in improving its status from